Influence of eight week core strength training on respiratory muscle strength in young soccer players - Bostanci, Ö.; Kabadayi, M.; Yilmaz, A. K.; Mayda, M. H.; Yilmaz, Ç.; Erail, S.; Karaduman, E. (International Journal of Applied Exercise Physiology, 2020)
Purpose: Core Strength Training (CST) has become a well-known training method in sport sciences and medicine. The aim of the present study was to examine the effects of CST program on the respiratory functions and muscle strength in young soccer player. Materials and methods: Thirty one male soccer players participated in this study. The subjects were divided into two groups as experimental group (EG, n=11) and control group (CG, n=11). An eight-week CST program was implemented in the EG. The CG subjects participated in their respective sport training routine. The samples` pulmonary function tests were administered with spirometry, while their respiratory muscle strength tests were administered by using intraoral barometer. All tests were measured both pre-test and post-test for all groups. Results: There were significant improvements in FVC, MIP and MEP between pre-test and post-test in EG (p<0.05). There were statistically differences in FEV1 and SVC between EG and CG in post-test (p<0.05). Difference was found in MEP between EG and CG in post-test (p<0.05.) Conclusion: CST was found to increase both some pulmonary functions and respiratory muscle strength. These results clearly indicate that CST positively affects pulmonary functions and especially respiratory muscles strength in young soccer player.